8.1k views
2 votes
Solve by using substitution -5x-y=12 y=-4x-9

User Brpaz
by
6.0k points

1 Answer

0 votes

Answer:

(-3, 3)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

-5x - y = 12

y = -4x - 9

Step 2: Solve for x

Substitution

  1. Substitute in y: -5x - (-4x - 9) = 12
  2. Distribute negative: -5x + 4x + 9 = 12
  3. Combine like terms: -x + 9 = 12
  4. Subtract 9 on both sides: -x = 3
  5. Divide -1 on both sides: x = -3

Step 3: Solve for y

  1. Define original equation: y = -4x - 9
  2. Substitute in x: y = -4(-3) - 9
  3. Multiply: y = 12 - 9
  4. Subtract: y = 3
User James Hull
by
5.0k points